Internalization and Reflection of Sufism-Based Character Education Values from Syi’Ir Tanpo Waton - Soraya, Irma; Abitolkha, Amir Maliki; Imaniar, Fahmi (Didaktika Religia, 2023)
Character formation is the ultimate goal of the educational process, but the internalization of character into social attitudes and behavior is still experiencing difficulties. Ahlus Shofa Al Wafa Pondok pesantren, Sidoarjo can make efforts to internalize character traits through Syi’ir Tanpo Waton into the behavior of students and congregation. Therefore, this study aims to explain the internalization of character education values in Syi’ir Tanpo Waton concerning Sufism in the language dauroh congregation of Ahlus Shofa Al Wafa Pondok pesantren and examine the reflection of character education values in Syi’ir Tanpo Waton in relation to Sufism on the Sufistic behavior of the language dauroh congregation of Ahlus Shofa Al Wafa Pondok pesantren. This research is qualitative with multi-approaches, namely normative-manuscript and phenomenological approaches. Primary data is taken from the narrative of the main source, namely the caregiver of the Ahlus Shofa Al Wafa Pondok pesantren and the principal. The results showed that internalization was carried out through the involvement and habituation of the congregation in activities in the Pondok pesantren, including the Foundation organization. The reflection of value of character education in the congregation is reflected through its behavior both concrete and abstract.